RATIO CONCEPT «EXTREMISM» AND «TERRORISM» - Elamanov, Nurlan (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
In the article, the author attempted to make a rational conclusion such as emphasizing the concept of terrorism as a significant expression of extremism, interrelation of mentioned concepts and consideration of the current situation in today’s society.